TNFRSF6 induces mitochondrial dysfunction and microglia activation in the in vivo and in vitro models of sepsis-associated encephalopathy: TNFRSF6 promotes sepsis-associated encephalopathy - Yu, Danfeng; Ji, Yanmei; Zhang, Jing; Huang, Xiaochuan (Cellular and Molecular Biology, 2024)
Sepsis-associated encephalopathy (SAE) is a serious complication of sepsis. The tumour necrosis factor receptor superfamily member 6 (TNFRSF6) gene encodes the Fas protein, and it participates in apoptosis induced in different cell types. This study aimed to explore TNFRSF6 function in SAE. The SAE mouse model was established by intraperitoneal injection of LPS in TNFRSF6−/− mice and C57BL/6J mice. Microglia were treated with LPS to establish the cell model. The learning, memory and cognitive functions in mice were tested by behavioral tests. Nissl staining was utilized for determining neuronal injury. Microglial activation was tested by immunofluorescence assay. ELISA was utilized for determining TNF-α, IL-1β, IL-6, and IL-10 contents. Mitochondrial dysfunction was measured by mitochondrial oxygen consumption, ATP content, ROS production, and JC-1 assay. TNFRSF6 was upregulated in the LPS-induced mouse model and cell model. TNFRSF6 deficiency notably alleviated the impaired learning, memory and cognitive functions in SAE mice. Furthermore, we found that TNFRSF6 deficiency could alleviate neuronal injury, microglial activation, and inflammation in SAE mice. Additionally, mitochondrial dysfunction in the SAE mice was improved by TNFRSF6 depletion. In the LPS-induced microglia, we also proved that TNFRSF6 knockdown reduced inflammatory response inhibited ROS production, and alleviated mitochondrial dysfunction. TNFRSF6 induced mitochondrial dysfunction and microglia activation in the in vivo and in vitro models of SAE.